Check sibling questions

Three vectors a, b and c satisfy the condition a + b + c = 0. Evaluate

Example 29 - Chapter 10 Class 12 Vector Algebra - Part 2
Example 29 - Chapter 10 Class 12 Vector Algebra - Part 3

Example 29 - Chapter 10 Class 12 Vector Algebra - Part 4

Example 29 - Chapter 10 Class 12 Vector Algebra - Part 5
Example 29 - Chapter 10 Class 12 Vector Algebra - Part 6
Example 29 - Chapter 10 Class 12 Vector Algebra - Part 7


Transcript

Example 29 (Method 1) Three vectors π‘Ž βƒ—, 𝑏 βƒ— and 𝑐 βƒ— satisfy the condition π‘Ž βƒ— + 𝑏 βƒ— + 𝑐 βƒ— = 0 βƒ— . Evaluate the quantity ΞΌ = π‘Ž βƒ— ⋅𝑏 βƒ— + 𝑏 βƒ— β‹… 𝑐 βƒ— + 𝑐 βƒ— β‹… π‘Ž βƒ—, if |π‘Ž βƒ—|=1, |𝑏 βƒ—|= 4 and |c βƒ—|= 2.Given |π‘Ž βƒ—|=1, |𝑏 βƒ—|= 4 and |c βƒ—|= 2 Also, π‘Ž βƒ— + 𝑏 βƒ— + 𝑐 βƒ— = 0 βƒ— So, |𝒂 βƒ—" + " 𝒃 βƒ—" + " 𝒄 βƒ— | = |𝟎 βƒ— | = 0 Now, |𝒂 βƒ—+𝒃 βƒ—+𝒄 βƒ— |2 = (𝒂 βƒ— + 𝒃 βƒ— + 𝒄 βƒ—) . (𝒂 βƒ— + 𝒃 βƒ— + 𝒄 βƒ—) = π‘Ž βƒ—. π‘Ž βƒ— + π‘Ž βƒ— . 𝑏 βƒ— + π‘Ž βƒ— . 𝑐 βƒ— + 𝑏 βƒ— . π‘Ž βƒ— + 𝑏 βƒ— . 𝑏 βƒ— + 𝑏 βƒ— . 𝑐 βƒ— + 𝑐 βƒ— . π‘Ž βƒ— + 𝑐 βƒ— . 𝑏 βƒ— + 𝑐 βƒ— . 𝑐 βƒ— = π‘Ž βƒ—. π‘Ž βƒ— + π‘Ž βƒ— . 𝑏 βƒ— + 𝒄 βƒ— . 𝒂 βƒ— + 𝒂 βƒ— . 𝒃 βƒ— + 𝑏 βƒ— . 𝑏 βƒ— + 𝑏 βƒ— . 𝑐 βƒ— + π‘Ž βƒ— . 𝑐 βƒ— + 𝒃 βƒ— . 𝒄 βƒ— + 𝑐 βƒ— . 𝑐 βƒ— = π‘Ž βƒ— . π‘Ž βƒ— + 𝑏 βƒ— . 𝑏 βƒ— + 𝑐 βƒ— . 𝑐 βƒ— + 2π‘Ž βƒ—. 𝑏 βƒ— + 2𝑏 βƒ—. 𝑐 βƒ— + 2𝑐 βƒ—. π‘Ž βƒ— = 𝒂 βƒ— . 𝒂 βƒ— + 𝒃 βƒ— . 𝒃 βƒ— + 𝒄 βƒ— . 𝒄 βƒ— + 2(π‘Ž βƒ—. 𝑏 βƒ— + 𝑏 βƒ—. 𝑐 βƒ— + 𝑐 βƒ—. π‘Ž βƒ—) = |𝒂 βƒ— |𝟐 + |𝒃 βƒ— |𝟐 + |𝒄 βƒ— |𝟐 + 2 (π‘Ž βƒ—. 𝑏 βƒ— + 𝑏 βƒ—. 𝑐 βƒ— + 𝑐 βƒ— . π‘Ž βƒ—) = 12 + 42 + 22 + 2(π‘Ž βƒ—. 𝑏 βƒ— + 𝑏 βƒ—. 𝑐 βƒ— + 𝑐 βƒ—. π‘Ž βƒ—) = 1 + 16 + 4 + 2(π‘Ž βƒ—. 𝑏 βƒ— + 𝑏 βƒ—. 𝑐 βƒ— + 𝑐 βƒ—. π‘Ž βƒ—) = 21 + 2 (𝒂 βƒ—. 𝒃 βƒ— + 𝒃 βƒ—. 𝒄 βƒ— + 𝒄 βƒ—. 𝒂 βƒ—) So, |π‘Ž βƒ—+𝑏 βƒ—+𝑐 βƒ— |2 = 21 + 2 (π‘Ž βƒ—. 𝑏 βƒ— + 𝑏 βƒ—. 𝑐 βƒ— + 𝑐 βƒ—. π‘Ž βƒ—) Now, given that |𝒂 βƒ—" + " 𝒃 βƒ—" + " 𝒄 βƒ— | = 0 |π‘Ž βƒ—" + " 𝑏 βƒ—" + " 𝑐 βƒ— |2 = 0 21 + 2 (𝒂 βƒ—. 𝒃 βƒ— + 𝒃 βƒ—. 𝒄 βƒ— + 𝒄 βƒ—. 𝒂 βƒ—) = 0 2(π‘Ž βƒ—. 𝑏 βƒ— + 𝑏 βƒ—. 𝑐 βƒ— + 𝑐 βƒ—. π‘Ž βƒ—) = βˆ’21 (π‘Ž βƒ—. 𝑏 βƒ— + 𝑏 βƒ—. 𝑐 βƒ— + 𝑐 βƒ—. π‘Ž βƒ—) = (βˆ’21)/2 Therefore, 𝝁 = 𝒂 βƒ—. 𝒃 βƒ— + 𝒃 βƒ—. 𝒄 βƒ— + 𝒄 βƒ— . 𝒂 βƒ— = (βˆ’πŸπŸ)/𝟐 Example 29 (Method 2) Three vectors π‘Ž βƒ—, 𝑏 βƒ— and 𝑐 βƒ— satisfy the condition π‘Ž βƒ— + 𝑏 βƒ— + 𝑐 βƒ— = 0 βƒ— . Evaluate the quantity ΞΌ = π‘Ž βƒ— ⋅𝑏 βƒ— + 𝑏 βƒ— β‹… 𝑐 βƒ— + 𝑐 βƒ— β‹… π‘Ž βƒ—, if |π‘Ž βƒ—|=1, |𝑏 βƒ—|= 4 and |c βƒ—|= 2.Given |π‘Ž βƒ—| = 1, |𝑏 βƒ—|= 4 and |c βƒ—|= 2 Also, ( π‘Ž βƒ— + 𝑏 βƒ— + 𝑐 βƒ— ) = 0 βƒ— Now, 𝒂 βƒ— . (𝒂 βƒ— + 𝒃 βƒ— + 𝒄 βƒ—) = π‘Ž βƒ— . π‘Ž βƒ— + π‘Ž βƒ—. 𝑏 βƒ— + π‘Ž βƒ— . 𝑐 βƒ— π‘Ž βƒ— . 0 βƒ— = π‘Ž βƒ—. π‘Ž βƒ— + π‘Ž βƒ—. 𝑏 βƒ— + π‘Ž βƒ—. 𝑐 βƒ— 0 = 𝒂 βƒ—. 𝒂 βƒ— + π‘Ž βƒ—. 𝑏 βƒ— + π‘Ž βƒ—. 𝑐 βƒ— 0 βƒ— = |𝒂 βƒ— |𝟐 + π‘Ž βƒ—. 𝑏 βƒ— + 𝒂 βƒ—. 𝒄 βƒ— (Using prop : π‘Ž βƒ— . π‘Ž βƒ— = |π‘Ž βƒ— |2 ) 0 βƒ— = |π‘Ž βƒ— |2 + π‘Ž βƒ—. 𝑏 βƒ— + 𝒄 βƒ—. 𝒂 βƒ— 0 = 12 + π‘Ž βƒ—. 𝑏 βƒ— + 𝑐 βƒ—. π‘Ž βƒ— 0 = 1 + π‘Ž βƒ—. 𝑏 βƒ— + 𝑐 βƒ—. π‘Ž βƒ— π‘Ž βƒ—. 𝑏 βƒ— + 𝑐 βƒ—. π‘Ž βƒ— = βˆ’1 Also, 𝒃 βƒ— . (𝒂 βƒ— + 𝒃 βƒ— + 𝒄 βƒ—) = 𝑏 βƒ— . π‘Ž βƒ— + 𝑏 βƒ—. 𝑏 βƒ— + 𝑏 βƒ— . 𝑐 βƒ— 𝑏 βƒ— . 0 βƒ— = 𝑏 βƒ—. π‘Ž βƒ— + 𝑏 βƒ—. 𝑏 βƒ— + 𝑏 βƒ—. 𝑐 βƒ— 0 = 𝒃 βƒ—. 𝒂 βƒ— + 𝑏 βƒ—. 𝑏 βƒ— + 𝑏 βƒ—. 𝑐 βƒ— 0 = 𝒂 βƒ—. 𝒃 βƒ— + 𝒃 βƒ—. 𝒃 βƒ— + 𝑏 βƒ—. 𝑐 βƒ— 0 = π‘Ž βƒ—. 𝑏 βƒ— + |𝒃 βƒ— |2 + 𝑏 βƒ—. 𝑐 βƒ— 0 = π‘Ž βƒ—. 𝑏 βƒ— + 42 + 𝑏 βƒ— . 𝑐 βƒ— 0 = π‘Ž βƒ—. 𝑏 βƒ— + 16 + 𝑏 βƒ— . 𝑐 βƒ— π‘Ž βƒ—. 𝑏 βƒ— + 𝑏 βƒ—. 𝑐 βƒ— = βˆ’16 Also 𝒄 βƒ— . (𝒂 βƒ—+ 𝒃 βƒ— + 𝒄 βƒ—) = 𝑐 βƒ— . π‘Ž βƒ— + 𝑐 βƒ— . 𝑏 βƒ— + 𝑐 βƒ— . 𝑐 βƒ— 𝑐 βƒ—. 0 βƒ— = 𝑐 βƒ—. π‘Ž βƒ— + 𝑐 βƒ—. 𝑏 βƒ— + 𝑐 βƒ—. 𝑐 βƒ— 0 = 𝑐 βƒ—. π‘Ž βƒ— + 𝒄 βƒ—. 𝒃 βƒ— + 𝑐 βƒ—. 𝑐 βƒ— 0 = 𝑐 βƒ—. π‘Ž βƒ— + 𝒃 βƒ—. 𝒄 βƒ— + 𝒄 βƒ—. 𝒄 βƒ— 0 = 𝑐 βƒ—. π‘Ž βƒ— + 𝑏 βƒ—. 𝑐 βƒ— + |𝒄 βƒ— |2 0 = 𝑐 βƒ—. π‘Ž βƒ— + 𝑏 βƒ— . 𝑐 βƒ— + 22 0 = 𝑐 βƒ—. π‘Ž βƒ— + 𝑏 βƒ— . 𝑐 βƒ— + 4 𝑐 βƒ—. π‘Ž βƒ— + 𝑏 βƒ—. 𝑐 βƒ— = βˆ’4 Adding (1), (2) and (3), (𝒂 βƒ—. 𝒃 βƒ— + 𝒄 βƒ—. 𝒂 βƒ—) + (𝒂 βƒ—. 𝒃 βƒ— + 𝒃 βƒ—. 𝒄 βƒ—) + (𝒄 βƒ—. 𝒂 βƒ— + 𝒃 βƒ—. 𝒄 βƒ—) = βˆ’1 + (–16) + (–4) 2π‘Ž βƒ—. 𝑏 βƒ— + 2𝑐 βƒ—. π‘Ž βƒ— + 2𝑏 βƒ—. 𝑐 βƒ— = βˆ’21 2(π‘Ž βƒ—. 𝑏 βƒ— + 𝑏. 𝑐 βƒ— + 𝑐 βƒ—. π‘Ž βƒ—) = βˆ’21 π‘Ž βƒ—. 𝑏 βƒ— + 𝑏 βƒ—. 𝑐 βƒ— + 𝑐 βƒ—. π‘Ž βƒ— = (βˆ’21)/2 Therefore, 𝝁 = 𝒂 βƒ—. 𝒃 βƒ— + 𝒃 βƒ—. 𝒄 βƒ— + 𝒄 βƒ— . 𝒂 βƒ— = (βˆ’πŸπŸ)/𝟐

Davneet Singh's photo - Teacher, Engineer, Marketer

Made by

Davneet Singh

Davneet Singh is a graduate from Indian Institute of Technology, Kanpur. He has been teaching from the past 12 years. He provides courses for Maths and Science at Teachoo.